Teor de ácido cianídrico e taxa de crescimento do híbrido de sorgo x capim sudão durante o outono - Simili, Flávia Fernanda; Lima, Maria Lúcia Pereira; de Medeiros, Maria Izabel Merino; de Paz, Claudia Cristina Paro; Ruggieri, Ana Claudia [UNESP]; Reis, Ricardo Andrade [UNESP] (FapUNIFESP (SciELO), 2013)
In central Brazil after soybean or other annual agricultural species is harvested, sorghum hybrids are planted in the fall in order to establish pastures for grazing animals. This study conducted for two consecutive years aimed at quantifying the contents of hydrocyanic acid in the leaves and determining plant height, forage dry matter yield and the leaf/stem ratio for sorghum hybrid 1P400 at different ages. Statistical analysis was performed by regression analysis based on plant age. Leaf HCN content decreased with plant growth, ranging from 205.0 and 230.3 mg HCN/100 g leaf DM at two weeks old to 5.9 and 6.1 mg HCN/100 g leaf DM at five weeks old in the first and second year, respectively. The average heights measured varied from 60 and 56 cm, in the 4th week, to 117 and 151 cm, in the 8th week, during the first and second experimental year, respectively. Forage mass increased linearly with age and displayed average of 1.411 and 1.637 kg DM/ha in the first year and, 2.905 and 3.640 kg DM/ha in the second year, during the 7th and 8th week, respectively. Leaf proportion decreased while stem increased linearly with plant age. The leaf/stem ratio decreased with plant growth, elongation and increasing stem weight. The sorghum hybrid should be grazed only after five weeks or when the plant height is above 80 cm, in order to avoid the risk of cyanide poisoning.
Hydrocyanic acid content and growth rate of sorghum x sudangrass hybrid during fall
Keywords: Annual grasses; Cyanogenic plants; Picro-sodium test; Toxic plant